The Role of Sonic Hedgehog Pathway in the Development of the Central Nervous System and Aging-Related Neurodegenerative Diseases - Yang, Chen; Qi, Yan; Sun, Zhitang (Frontiers in Molecular Biosciences, 2021)
The Sonic hedgehog (SHH) pathway affects neurogenesis and neural patterning during the development of the central nervous system. Dysregulation of the SHH pathway in the brain contributes to aging-related neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. At present, the SHH signaling pathway can be divided into the canonical signaling pathway and non-canonical signaling pathway, which directly or indirectly mediates other related pathways involved in the development of neurodegenerative diseases. Hence, an in-depth knowledge of the SHH signaling pathway may open an avenue of possibilities for the treatment of neurodegenerative diseases. Here, we summarize the role and mechanism of the SHH signaling pathway in the development of the central nervous system and aging-related neurodegenerative diseases. In this review, we will also highlight the potential of the SHH pathway as a therapeutic target for treating neurodegenerative diseases.